2001
DOI: 10.1007/s004270100176
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily conserved nuclear migration genes required for early embryonic development in Caenorhabditis elegans

Abstract: The nudF and nudC genes of the fungus Aspergillus nidulans encode proteins that are members of two evolutionarily conserved families. In A. nidulans these proteins mediate nuclear migration along the hyphae. The human ortholog of nudF is Lis1, a gene essential for neuronal migration in the developing cerebral cortex. The mammalian ortholog of nudC encodes a protein that interacts with Lis1. We have identified orthologs of nudC and Lis1 from the nematode Caenorhabditis elegans. Heterologous expression of the C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
54
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 25 publications
5
54
0
Order By: Relevance
“…1F). RNAi of lis-1 caused embryonic lethality as previously reported (12). However, some escapers that had milder RNAi effects showed significant suppression of the guidance defect (Fig.…”
Section: Transgenic Mdisc1 In C Elegans Motor Neurons Functions In Asupporting
confidence: 76%
See 1 more Smart Citation
“…1F). RNAi of lis-1 caused embryonic lethality as previously reported (12). However, some escapers that had milder RNAi effects showed significant suppression of the guidance defect (Fig.…”
Section: Transgenic Mdisc1 In C Elegans Motor Neurons Functions In Asupporting
confidence: 76%
“…Among these genes, homologs of two well-known mDISC1-interacting genes, pde-4 and lis-1, are present in the C. elegans motor neurons (12) (Fig. S2).…”
Section: Transgenic Mdisc1 In C Elegans Motor Neurons Functions In Amentioning
confidence: 99%
“…The connection between LIS1 homologs and cytoplasmic dynein was first made in the filamentous fungus Aspergillus nidulans and the budding yeast Saccharomyces cerevisiae by genetic studies (Xiang et al 1995a;Geiser et al 1997). Further studies have demonstrated that LIS1 and its homologs in higher eukaryotic systems are also involved in cytoplasmic dynein function, and physical interactions between LIS1 and dynein/dynactin have been shown (Liu et al 2000;Sasaki et al 2000;Dawe et al 2001;Tai et al 2002;reviewed by Wynshaw-Boris and Gambello 2001;Gupta et al 2002;Tsai and Gleeson 2005;Vallee and Tsai 2006). Recently, purified LIS1 has been shown to enhance the microtubule-stimulated ATPase activity of the dynein motor (Mesngon et al 2006).…”
mentioning
confidence: 99%
“…Whether the apparently different biochemical interactions of Lis1 are functionally related remains to be seen. Proteins homologous to vertebrate Lis1 have been identified in several organisms, including Saccharomyces cerevisiae (29), Aspergillus nidulans (30), Caenorhabditis elegans (31), and Drosophila (32). In yeast and A. nidulans Lis1 homologues play a role in dynein-mediated nuclear migration (30,(33)(34)(35).…”
mentioning
confidence: 99%
“…In the mouse, Lis1 also interacts with the nuclear migration proteins NUDC (36) and mNudE-L (37) suggesting a similar role. Abrogation of lis-1 in C. elegans results in embryonic lethality, sterility, altered vulval morphology, uncoordinated movement, and nuclear positioning defects during early embryonic cell divisions (31). Lis1 in Drosophila is also essential for normal development (32).…”
mentioning
confidence: 99%